Reformasi Pendidikan Islam Dalam Menghadapi Era Globalisasi Di Indonesia - Mardiah Astuti; Ibrahim Ibrahim; Herlina Herlina; Alecia Septiana; Fheny Irawandi; Sherly Margareta; Rendika Zulipran (Jambura Journal of Educational Management, 2023)
This article discusses the Reform of Indonesian Islamic Education in Facing Globalization. In the era of globalization, Islamic education has a number of difficulties which are discussed in this article. Islamic education reform as an effort to change or improve the Islamic education system with the aim of improving the quality of education, updating the curriculum, teaching methods, and increasing human resources involved in the process of Islamic education. Islamic education reform is an important part of sustainable education development, so that the goal of improving the entire education system can bring great benefits to the whole society and the whole country. Islamic education reform is very important in the era of globalization, because the era of globalization has brought new challenges to Islamic education. The aim of education in the context of globalization is always to achieve a state of harmony between needs and results by reforming programs and actions, activities so as not to lose their relevance to the needs of local, national, regional and international communities.